Colonoscopic examination of rectal bleeding in children: A report of two cases - Abdulfatai B Olokoba; Olusegun A Obateru; Mathew O Bojuwoye; Olatunde K Ibrahim; Olasunkanmi M Babalola (Wolters Kluwer Medknow Publications, 2012)
Rectal bleeding in children is a frightening and cause of great concern, and of parental anxiety. In this report, we present the value of colonoscopy to unravel the diagnostic conundrum often associated with rectal bleeding in children.